Atherogenic Index Profiles as Predictor of Cardiovascular Risk in Premenopausal and Menopausal Women - Thaslifa; Mutmainnah Abbas; Alfyan Rahim (Universitas Nahdlatul Ulama Surabaya, 2022)
Cardiovascular disease was a disease with impaired function of the heart and blood vessels. Cardiovascular disease was more common in women. Postmenopausal women have a higher risk of cardiovascular disease than premenopausal women. This is because postmenopausal women lack the hormone estrogenin regulating lipid metabolism factors. Decreased production of the hormone estrogen will cause changes in the lipid profile in the blood. Several studies have shown that assessment with the Atherogenic Index (IA) is a good predictor of cardiovascular disease. The atherogenic index was obtained by calculating the TG/HDL-C log. This assessment proved to be more sensitive in assessing the risk of cardiovascular disease compared to the respective lipid profile calculations. This study aimed to compare the profile of the Atherogenic Index in premenopausal women with menopause. This research used the Cross-Sectional Study research method which was presented in the form of data, tables, and narratives. The study results on each 40 menopausal and premenopausal women respectively showed that the comparison value of the atherogenic index in the two categories of subjects was <0.05 (0.00). This showed that there is a significant difference in the mean atherogenic index between postmenopausal and premenopausal women.